Maxim Berezovsky’s Concerto “Do not Forsake Me at the Time of Old Age” in the Context of the Stylistic Principles of Russian Music of the 18th Century - Shindin, Boris A. (Music Scholarship / Problemy Muzykal’noj Nauki, 2018)
The process of acquisition of new artistic space by 18th century Russian composers was accompanied by many ambiguous and contradictory trends. The correlated phenomena of the new emerging culture of a new era and the not forsaken traditions of the musical past disclosed their potential predominantly in the direction of the following two styles: the Baroque and the Classicist. An appropriate interpretation of the numerous musical works composed at that time takes place through comparison of the tendencies of Russian and Western European culture. The peculiarity of the Russian Baroque was noted in the research works of Dmitri Likhachev. His works formed the view according to which the Russian Baroque, in contrast to the European variety, possessed an optimistic character with a very sparsely expressed tragic element. However, this picture of a harmonious, light style does not correspond with the intense tragic feelings inherent in the choral concerto by Maxim Berezovsky “Do not Forsake Me at the Time of Old Age,” which combines features of baroque and classicism. The basis of the Concerto is formed by the literary text it was set to – verses 9–13 of Psalm 70, which recount the tragic circumstances of the life of David. The main vector of verbal explanation discloses the theme of exile, which has always been popular in dramatic forms of art. The musical means endowed with expression are reinforced with intense melodic development, covering all four movements of the cycle. The emotional intensity of the Concerto makes it possible to place it into an artistic domain that is congruent with the tragic element of Russian music, the segment of it which represents motives of individuals in human history. The theme of tragedy runs continuously throughout the entirety of Russian music. In the 19th century the tragedy of the personality is most clearly expressed in the music of Piotr Tchaikovsky, while in the 20th century, they are presented most vividly the music of Dmitri Shostakovich. The pinnacle of the tragic perception of the world in the 18th century is formed by this particular choral cycle by Maxim Berezovsky. Keywords: Maxim Berezovsky, choir concerto, Russian music, Russian Baroque, Psalm 70, tragic imagery, the genetic codes of art, Dmitri Shostakovich, Piotr Tchaikovsky.